The historical preconditions of creation of the Organization of Islam Conference - Zhumagulova, K.B.; Nazarov, Ye.Zh. (Вестник Карагандинского университета, 2015)
Creation of the OIC became an important step for the formation of foreign policy paradigm of muslim states. All the steps to create the OIC in international relations as the main organization of islamic countries made within the concept of «islamic solidarity». The article examines as historical so political preconditions for the establishment of the OIC, as well as main objectives and reasons that gave rise to organization of muslim states to create the OIC. In this regard, the OIC under the concept of «islamic solidarity» for the right to occupy a central place in the islamic world and it is a key organ of cooperation of the states with a large number of muslim population.
Ислам Конференциясы Ұйымының құрылуының тарихи алғышарттары
Исторические предпосылки создания Организации Исламская Конференция
Keywords: foreign policy; modern international relations; the organization of the Islamic Conference; an international organization; integration; middle East; Islam; history of the Islamic world; pan-Islamism